Opodatkowanie jednostek gospodarki państwowej w socjalizmie: [Taxation of socialized economy units] (Studia Prawnicze / The Legal Studies, 1981)
This paper constitutes a trial of theoretical analysis of three possible systems of taxation of state economy units. The analysis takes into account objective character of the payments of state enterprises to state budget in conditions of socialized economy. The first, theoretical only and not used in practice, is a system of a single tax fulfilling the postulates of simplicity, cheapness and organizational efficiency. A turnover tax could first of all play this role and that is why it is closer looked at in this paper. Second is a system of so called „double-channeled" taxation (including a turnover tax and payments from profit). This system was widely used in the socialist countries until fundamental economic reform undertaked in the seventees. In this paper both its adventages and disadventages are presented. The third possible is a developed system of taxes imposed on state  enterprises in particular taking into consideration taxation of elements of production. This system is widely used now in the majority of socialist countries as an instrument of indirect management of economy. Here, particular attention was drawn to conditions of efficiency of this instrument, mainly, its stimulating influence on effective activity of the enterprises. In the Author's opinion low efficiency of such influence in up-to-date practice results from the difficulties connected with full implementation of the discussed conditions.